Teacher stress interventions: A systematic review - Embse, Nathaniel; Ryan, Shannon V.; Gibbs, Tera; Mankin, Ariel (Psychology in the schools, 2019)
Due to the increased pressure from test‐based accountability practices, teachers have reported high levels of stress and burnout. High teacher stress has an impact on school outcomes, including links to absenteeism, burnout, school climate, and teacher behavior management. Teacher stress interventions may be an important first step toward reducing these negative outcomes. Although there have been several recent intervention studies in the domain of teacher stress, there has been no systematic review to compare the type and effectiveness of teacher stress interventions. Included within this review are interventions from a variety of modalities such as knowledge‐based, behavioral, cognitive‐behavioral, and mindfulness approaches. Results indicated that the most effective interventions were in the mindfulness, behavioral, and cognitive‐behavioral domains. Interventions which delivered solely informational content were among the least effective.